2007
DOI: 10.1111/j.1747-0803.2007.00122.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete Heart Block Due to Lyme Carditis in Two Pediatric Patients and a Review of the Literature

Abstract: Carditis is a common manifestation of adult patients with Lyme disease affecting 4-10% of Lyme patients in the United States. However, children with Lyme disease rarely present with acute carditis. The management of pediatric patients with complete heart block (CHB) secondary to Lyme carditis has not been well described. We report the acute management of 2 pediatric patients that presented in CHB secondary to Lyme disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…6,7 This knowledge is useful when counseling patients about the expected time course for improvement and reinforces the adult experience that permanent pacemaker implantation is rarely required. 4,19,28 Isolated case reports suggest that disturbances in atrioventricular conduction can rarely be permanent after Lyme carditis, as we saw with 1 patient who had persistent second-degree AVB.…”
Section: Figurementioning
confidence: 83%
See 2 more Smart Citations
“…6,7 This knowledge is useful when counseling patients about the expected time course for improvement and reinforces the adult experience that permanent pacemaker implantation is rarely required. 4,19,28 Isolated case reports suggest that disturbances in atrioventricular conduction can rarely be permanent after Lyme carditis, as we saw with 1 patient who had persistent second-degree AVB.…”
Section: Figurementioning
confidence: 83%
“…2,19,26,27 Although corticosteroids are sometimes advocated, there is no evidence that they are beneficial in patients with Lyme carditis and advanced heart block. 3,7,22,28 No patient in this series received corticosteroids.…”
Section: Figurementioning
confidence: 91%
See 1 more Smart Citation
“…Lyme carditis is the commonest cause of acquired complete AV heart block in pediatric patients in the United States and occurs in 2% to 10% of patients with Lyme disease. 8,9 In the systematic review of the literature of Batra et al, 10 they identified a total of 40 children with acute myocarditis complicated by an advanced AV block; an etiology of myocarditis was identified in only 12 (30%) of the 40 children, with the most common pathogens being coxsackie B virus (n = 4), respiratory syncytial virus (n = 2), and Mycoplasma pneumoniae (n = 2). Other rare causes of acquired complete AV block in children include acute rheumatic fever, 11 intracardiac yolk sac tumor, 12 endomyocardial fibrosis, 13 Teebi hypertelorism (hypertelorism, with a facial appearance that can resemble craniofrontonasal dysplasia, limb anomalies, urogenital defects), 14 Lafora disease, 15 familial dysautonomia, 16 and sevoflurane anesthesia.…”
Section: History and Physical Examinationmentioning
confidence: 98%
“…Silver and his colleagues found only 34 cases in the English literature describing documented cases of Lyme carditis in patients aged 23-47 years of age. They report on two male patients aged 15 and 17 who developed complete heart block [12].…”
Section: Dr Wolfe: How Common Is This Entity?mentioning
confidence: 99%